2022
DOI: 10.1177/03128962221135496
|View full text |Cite
|
Sign up to set email alerts
|

Modeling transitions in nation brand equity: An empirical assessment of the nation equity power grid

Abstract: The purpose of this study is to assess longitudinal nation brand performance by modeling transitions in nation brand equity and to develop a method for nation brand performance assessment. This study has two objectives: (1) to empirically test Steenkamp’s nation equity power grid conceptual framework; its categories (dominant, receding, niche, emerging, and weak nation brands), and their expected development trajectories, and (2) to identify new types of nation brands and development patterns to complement the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Through leveraging their most crucial nation brand predictor variables, nations with moderate and weak brand strength can best achieve their long-term objectives in terms of developing a more balanced nation brand and, perhaps, challenge some of the strong nation brands. While nation brand development is a lengthy process, recent studies have shown how certain nations have leapfrogged some of their peers in strengthening their nation brands (Juusola and Lahrech, 2022). For example, Juusola and Lahrech (2022) demonstrated that certain "booming nation brands" (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through leveraging their most crucial nation brand predictor variables, nations with moderate and weak brand strength can best achieve their long-term objectives in terms of developing a more balanced nation brand and, perhaps, challenge some of the strong nation brands. While nation brand development is a lengthy process, recent studies have shown how certain nations have leapfrogged some of their peers in strengthening their nation brands (Juusola and Lahrech, 2022). For example, Juusola and Lahrech (2022) demonstrated that certain "booming nation brands" (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…While nation brand development is a lengthy process, recent studies have shown how certain nations have leapfrogged some of their peers in strengthening their nation brands (Juusola and Lahrech, 2022). For example, Juusola and Lahrech (2022) demonstrated that certain "booming nation brands" (i.e. China and Finland) have strengthened their brand performance with a speed that surpassed the speed of their peer countries, which consequently placed them among the countries with strong nation brands.…”
Section: Resultsmentioning
confidence: 99%